2019
DOI: 10.4012/dmj.2017-324
|View full text |Cite
|
Sign up to set email alerts
|

<i>In vitro</i> and <i>in vivo</i> analysis of the biodegradable behavior of a magnesium alloy for biomedical applications

Abstract: The present study was designed to investigate the biodegradation behavior of Mg alloy plates in the maxillofacial region. For in vitro analysis, the plates were immersed in saline solution and simulated body fluid. For in vivo, the plates were implanted into the tibia, head, back, abdominal cavity, and femur and assessed at 1, 2, and 4 weeks after implantation. After implantation, the plate volumes and the formed insoluble salt were measured via micro-computed tomography. SEM/EDX analysis of the insoluble salt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…91 Surface morphology of the AZ31 alloy showed the formation of an insoluble Ca-P layer after 4 weeks of implantation which can further initiates bone formation. 76 The formation of the Ca-P layer was found on the implanted surface of AZ31 alloy after 60 days of implantation. 79 SEM and EDS analysis of ZEK100 alloys revealed a Ca-P rich surface layer with nuggets to needle-like structure on the implant surface after 9 and 12 months of implantations.…”
Section: Microstructural Evaluationmentioning
confidence: 94%
See 2 more Smart Citations
“…91 Surface morphology of the AZ31 alloy showed the formation of an insoluble Ca-P layer after 4 weeks of implantation which can further initiates bone formation. 76 The formation of the Ca-P layer was found on the implanted surface of AZ31 alloy after 60 days of implantation. 79 SEM and EDS analysis of ZEK100 alloys revealed a Ca-P rich surface layer with nuggets to needle-like structure on the implant surface after 9 and 12 months of implantations.…”
Section: Microstructural Evaluationmentioning
confidence: 94%
“…138 Sato et al, found many interconnected capillaries and granular fibrous tissues that help in the formation of collagen scar tissue that contains a lot of collagen fibres. 76 Histopathological analysis of the tissue of kidney and liver organs showed a normal structure and was not affected by leached Mg ions. 79 The histological analysis of the ZEK100 alloy showed structural alteration, formation of cavities and new bone formation after 9 months of implantation in the tibia of rabbits with no negative effects on animals.…”
Section: Histological Testsmentioning
confidence: 95%
See 1 more Smart Citation
“…The simulation method using SBF soaking in this study is well known as a in vitro assay for evaluation of bone-bonding ability of biomaterials, and has been already used widely for the study regarding the osteoconductivity [18][19][20][21] . Therapeutic condition for LIPUS for osseointegrarion was still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…This has significantly improved the corrosion resistance and mechanical properties of magnesium and its alloys, so magnesium and its alloys have again attracted attention as biodegradable medical materials in recent years. [11][12][13][14][15] Previous studies have confirmed that magnesium alloys have good biocompatibility, may promote osteocyte growth, and induce production of osteoblasts and osteocytes. [16][17][18][19][20] However, the osteogenesis and degradation behavior of magnesium alloy plate in vivo is unknown.…”
Section: Introductionmentioning
confidence: 99%